Konstruksi Citra Destinasi Wisata Gedung Juang45 Bekasi Dalam Berita Media Daring Tribunnews - Ralvin Januar Wijaya; Bernard Realino Danu Kristianto; Rustono Farady Marta; Sugeng Wahyudi (Universitas Medan Area, 2021)
Online media in the era of digitalization has become an alternative choice for people in seeking information to replace conventional mass media. This study aims to see the relationship of online media in the development of tourist destinations in Gedung Juang45 in Bekasi Regency. This research uses a qualitative descriptive method, with the Pan and Kosicki framing analysis technique. The online media studied was Tribunnews to see news narratives in the 2019 to 2020 period using discourse analysis. News was analyzed by selecting topics related to the development of the Gedung Juang45 in Bekasi Regency on the Tribunnews Online Media Content. There were two news stories in March and August 2019, which mostly criticized the Bekasi Regency Government (Pemkab. Bekasi). On the other hand, when entering February to December 2020, researchers managed to find 13 supporting news for Pemkab. Bekasi regarding the construction of the Gedung Juang45. The results showed that of the 13 news, there is the same narrative to form the image construction of the Pemkab. Bekasi in increasing tourism, especially the Gedung Juang45 Tourism Destination.